The use of dental examination in the human remains body identification - Lewandowski, Bogumił; Brodowski, Robert (European Journal of Clinical and Experimental Medicine, 2011)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Victims of car accidents, catastrophies and natural disasters many times couse difficult problem for the forensic medicine concerned with the human body identification. The aim of this thesis is to show the ability of human body identification using dental check and the dental documentation. The case concerns a man who was lost and the body of which was drowned and later on found and taken out of a river. After the analysis of the past sicknesses and the dental analysis of the body it was stated that the body taken out of the river is the same as the lost man.